THE EFFECT OF PROBIOTIC BOSTER BIO LACTO IN DIFFERENT DOSES OF FEED ON THE GROWTH AND SURVIVAL RATE OF NILEM FISH (Osteochilus hasselti) IN THE RECIRCULATION SYSTEM - Novika A Sitanggang; Iskandar Putra; Mulyadi Mulyadi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
The aims of the research was determine the optimal Bio Lacto probiotic boster dose on comersial feed additing to improve growth rate and survival of Nilem Fish (Osteochilus hasselti) in recirculation systems. The research was conducted for 40 days from April to May 2020. This research was conducted at the laboratory of aquaculture technology Faculty of Fisheries and Marine Sciences, Riau University. The experiment method using a Completely Randomized Design (RAL) which consists of 4 treatments and 3 replications, is treatment 1). 0 mL/kg of feed (control); 2). 7 mL/kg of feed; 3). 9 mL/kg of feed; 4). 11 mL/kg of feed. The results of this study showed the addition of probiotics Bio Lacto in the feed to give significant effect to the growth rate of Nilem Fish (Osteochilus hasselti) reared in the recirculation system, but had no significant effect on the survival of Nilem fish seeds. The best treatment was found in the addition of probiotic at a dose of 11 ml / kg of feed giving absolute weight growth of 4.08 g, absolute length growth of 3.10 cm, feed digestibility of 75.5%, protein digestibility of 88.7%, specific growth rate of 3.31%/day, feed efficiency of 71.36%, feed conversion ratio of 1.40, and survival of 82.22%.